again, incorrect
when you add/subtract terms they must be "like"
the variables and exponents do not change.
3x + 2y + 16x^3z + 6y
= 3x + 8y + 16x^3z
(the only terms that were "like" were the y terms )
3x + 2y + 16x^3z + 6y =
ANSWER: 19x + 8y + 3z
6 answers
If the problem has no typos, it can reduce to:
16x^3z + 8y + 3x
16x^3z + 8y + 3x
the question is i wrote it wrong
3x + 2y + 16x + 3z + 6y =
3x + 2y + 16x + 3z + 6y =
So what is your answer?
I see three kind of terms, x's , y's and z's
I see three kind of terms, x's , y's and z's
19x + 8y + 3z
Right.